The impact of temperature on the metabolism of volatile fatty acids by polyphosphate accumulating organisms (PAOs) - Wang, Li (2021)
This study investigated the effects of different carbon sources on enriched Accumulibacter PAO cultures at high temperature (30 °C) and compared the carbon transformation with low temperature (20 °C) cases reported in literature, revealing several key metabolic differences. While PAOs seemed to prefer propionate anaerobically as compared to other VFAs at high temperature, high aerobic glycogen replenishment was realized with propionate as the anaerobic carbon source, a trait not previously observed at low temperatures. Therefore, it was found that propionate is not correlated with high P removal by Accumulibacter PAO at high temperatures. A combined substrate of acetate, propionate and perhaps butyrate seemed to be a better carbon source combination, since the total VFA uptake rate increased by up to 46%, and this increased the aerobic P-removal efficiency by up to 38.4% and reduced the glycogen recovery by more than 63% compared to the use of only propionate as substrate. This study improves our understanding of how to stimulate successful EBPR operation in warm climates by augmenting the P removal performance of PAOs.